The Acquisition of English Adjective Placement on the Early Acquisition of Bilingual Indonesian Language - English Child - Yanuar, Ivo Dinasta (Universitas Bunda Mulia, 2023)
This paper investigates the development of adjective on the early acquisition of bilingual Indonesian language – English child in Indonesian environment. It was longitudinal study to investigate how the child developed his adjective on two languages simultaneously and to know whether the language dominance influences the acquisition of English which become the weak language. It also used descriptive qualitative by writing daily word production of the kid. The hypothesis of this research was Indonesian language would disturb the development of English adjective on participant’s early acquisition. In this context, the participant was exposed with English in very limited time while his friends and environment speak full Indonesian language. The participant was an Indonesian boy who was exposed with Indonesian language and English from birth. His mommy, and sister were bilingual people who speak Indonesian language and English at home. Meanwhile, his daddy was multilingual person who speak Indonesian language – Lampungese language – English. However, his daddy never taught Lampungese language at home. This study was designed for 17 months starting from respondent’s age 1;8 until 3;0. The result shows that the participant developed both languages very well although English adjective form affected the place of Indonesian adjective form in which its exposure was higher than English as foreign language.